Evaluation of Wet Mount and Concentration Techniques of Stool Examination for Intestinal Parasites Identification at Debre Markos Comprehensive Specialized Hospital, Ethiopia - Demeke, Gebreselassie (Infect Drug Resist, 2021)
BACKGROUND: Intestinal parasitic infection has serious medical and public health impacts in developing countries. Intestinal parasites were under reported via direct wet mount method due to its poor sensitivity. So, the selection of a more sensitive and reliable diagnostic method is essential. OBJECTIVE: The aim of the study was to evaluate the diagnostic performance of wet mount and concentration techniques of stool examination for intestinal parasites identification. METHODS: A cross-sectional study among 797 pregnant women was conducted from October 2018 to February 2019 at Debre Markos Comprehensive Specialized Hospital. The study participants were selected by using a systematic random sampling technique. Stool sample was processed by using Wet Mount (WM) and Formol-Ether Concentration (FEC) techniques. Data was entered into Epi-data version 3.1 and analysis using SPSS version 20.0. The sensitivity, specificity, positive predictive value, and negative predictive value were determined against the combined result as “Gold” standard. Kappa value was determined to estimate the agreement of the diagnostic methods. RESULTS: The overall prevalence of intestinal parasites (IP) was 35.2% with a combined method. By using WM and FEC the prevalence of IP was 13.1% and 25.7%, respectively. The sensitivity and negative predictive value of WM method were 37.1% and 74.6%, and for FEC method 73.5% and 87.5%, respectively. Test efficiency of direct WM and FEC were 77.9% and 90.7%, respectively. The agreement of WM and FEC techniques with combined technique were moderate (κ=0.434) and perfect (κ=0.783), respectively. CONCLUSION: The prevalence of intestinal parasites was under-reported by wet mount technique. The diagnostic performance of FEC technique for the diagnosis of intestinal parasites in pregnant women was notably high as compared to WM technique in the present study. Therefore, the WM and FEC combined method should be used as a routine diagnostic technique for the diagnosis of intestinal parasites identification.